CARACTERIZAÇÃO DE MISTURAS DE AMIDOS DE FEIJÃO E TUBEROSAS (MANDIOCA E BATATA-DOCE) E SUA APLICAÇÃO NA OBTENÇÃO DE BIOFILMES - Bedin, Ana Claudia (2014)
Starch is a storage reserve polysaccharide of higher plants and the main component of the carbohydrate portion of the daily diet, being present in roots, tubers, seeds and fruits. Starch is naturally found in the form of semi-crystalline granules and has physicochemical properties that vary with the botanical source of its origin. Mixtures of starches from different sources have complementary features that are not observed in native starches. Common bean (Phaseolus vulgaris L.) is a starchy legume (pulse) consumed regularly by most of the Brazilian population in cooked form. During storage, the seeds can acquire the defect known as "hard to cook" (HTC), making them undesirable for consumption. The extraction of starch from HTC bean can be an alternative to the use of these seeds. In this work the extraction of starch from common bean was performed and evaluated to optimize the extraction using design of experiments. Technological properties of the mixtures were also evaluated considering different proportions of starches from beans and tuberous raw materials, i.e., sweet potato (Ipomoea batatas (L.) Lam) and cassava (Manihot esculenta C.). Biofilms from mixtures of those starches was produced and their mechanical and barrier properties evaluated.